Indications and clinical outcomes of indwelling pleural catheter placement in patients with malignant pleural effusion in a cancer setting hospital. (28th August 2020) - Akram, Muhammad Junaid; Khalid, Usman; Bakar, Muhammad Abu; Butt, Faheem Mahmood; Ashraf, Mohammad Bilal; Khan, Faheem
Abstract: Background: The placement of indwelling pleural catheters (IPC) is an effective outpatient approach for the management of malignant pleural effusions (MPE). Aims: The indications and outcome of IPC in patients with MPE. Risk stratifications, prevention and management of IPC‐related complications. Methods: We retrospectively reviewed the clinical data of patients with MPE who underwent IPC insertion from July 2011 to July 2019. The multivariable logistic regression model was used to identify the independent risk factors associated with IPC infection and the Kaplan–Meier method to determine the overall survival. Results: A total of 102 patients underwent IPC insertion during the stipulated period and the mean age was 50.49 ± 14.36 years. Seventy‐one (69.6%) were females. The indications were Trap Lung in 38 (37.3%), failed talc pleurodesis in 28 (27.5%) and as a primary intervention in 36 (35.3%). The infection rate was 25.5%, of which 65.4% patients had nosocomial infections. Post‐IPC overall median survival time was 9.0 ± 2.50 weeks with highest in patients with trap lung (18 ± 1.50 weeks). In multivariable analysis, following variables were identified as a significant independent risk factor for IPC infection: Multiloculated MPE (AOR 2.80; 95%CI (1.00‐9.93), 0.04), trap lung (AOR 7.57; 95%CI (1.39‐41.25), 0.01), febrile neutropenia (FN) (AOR 28.55; 95%CI (4.23‐19.74), 0.001), IPC domiciliary education (AOR 0.18; 95%CI (0.05‐0.66), 0.001) and length of hospital stay (AOR 1.16; 95%CI (1.01‐1.33), 0.03). Conclusion: IPC insertion is an effective management for MPE with reasonable survival benefits. Infection is the most common complication, of which mostly are nosocomial infections with higher incidence in multiloculated effusions, trap lung, FN and with lack of domiciliary IPC care education.